Fungal Dimorphism and Virulence: Molecular Mechanisms for Temperature Adaptation, Immune Evasion, and In Vivo Survival - Gregory M. Gauthier (Mediators of Inflammation)
The thermally dimorphic fungi are a unique group of fungi within the Ascomycota phylum that respond to shifts in temperature by converting between hyphae (22–25°C) and yeast (37°C). This morphologic switch, known as the phase transition, defines the biology and lifestyle of these fungi. The conversion to yeast within healthy and immunocompromised mammalian hosts is essential for virulence. In the yeast phase, the thermally dimorphic fungi upregulate genes involved with subverting host immune defenses. This review highlights the molecular mechanisms governing the phase transition and recent advances in how the phase transition promotes infection.